The effects of low- and high-Glycemic Index foods on high-intensity intermittent exercise - Little, J. P.; Chilibeck, P. D.; Ciona, D.; Vandenberg, A.; Zello, G. A. (International Journal of Sports Physiology and Performance, 2009)
The glycemic index (GI) of a preexercise meal may affect substrate utilization and performance during continuous exercise. Purpose: To examine the effects of low- and high-GI foods on metabolism and performance during high-intensity, intermittent exercise. Methods: Seven male athletes participated in three experimental trials (low-GI, high-GI, and fasted control) separated by ~7 days. Foods were consumed 3 h before (~1.3 g·kg-1 carbohydrate) and halfway through (~0.2 g·kg-1 carbohydrate) 90 min of intermittent treadmill running designed to simulate the activity pattern of soccer. Expired gas was collected during exercise to estimate substrate oxidation. Performance was assessed by the distance covered on five 1-min sprints during the last 15 min of exercise. Results: Respiratory exchange ratio was higher and fat oxidation lower during exercise in the high-GI condition compared with fasting (P < .05). The mean difference in total distance covered on the repeated sprint test between low GI and fasting (247 m; 90% confidence limits, ±352 m) represented an 81% (likely, probable) chance that the low-GI condition improved performance over fasting. The mean difference between high GI and fasted control (223 m; ±385 m) represented a 76% (likely, probable) chance of improved performance. There were no differences between low and high GI. Conclusions: When compared with fasting, both low- and high-GI foods consumed 3 h before and halfway through prolonged, high-intensity intermittent exercise improved repeated sprint performance. High-GI foods impaired fat oxidation during exercise but the GI did not appear to influence high-intensity, intermittent exercise performance.